Помогите решить:преобразуйте выражение в многочлен стандартного вида во вложениях 535

1

Ответы и объяснения

2013-05-10T13:01:58+00:00

a) (m+n)^2+(m-n)^2=m^2+2mn+n^2+m^2-2mn+n^2=2m^2+2n^2

б) 2(a-1)^2+3(a-2)^2=2(a^2-2a+1)+3(a^2-4a+4)=2a^2-4a+2+3a^2-12a+12=5a^2-16a+14

в) 5(x-y)^2+(x-2y)^2=5(x^2-2xy+y^2)+x^2-4xy+4y^2=5x^2-10xy+5y^2+x^2-4xy+4y^2=6x^2-14xy+9y^2

г) 4(m-2n)^2-3(3m+n)^2=4(m^2-4mn+4n^2)-3(9m^2+6mn+n^2)=4m^2-16mn+16n^2-27m^2-18mn-3n^2=-23m^2-34mn+13n^2

д) 3(2a-b)^2-5(a-2b)^2=3(4a^2-4ab+b^2)-5(a^2-4ab+4b^2)=12a^2-12ab+3b^2-5a^2+20ab-20b^2=7a^2+8ab-17b^2

e) 4(3x+4y)^2-7(2x-3y)^2=4(9x^2+24xy+16y^2)-7(4x^2-12xy+9y^2)=36x^2+96xy+64y^2-28x^2+84xy-63y^2=8x^2+180xy+y^2

ж) 2(p-3q)^2-4(2p-q)^2-(2q-3p)(p+q)=2(p^2-6pq+9q^2)-4(4p^2-4pq+q^2)-(2pq+2q^2-3p^2-3pq)=2p^2-12pq+18q^2-16p^2+16pq-4q^2-2q^2+3p^2+pq=-11p^2+5pq+12q^2

з) 5(n-5m)^2-6(2n-3m)^2-(3m-n)(7m-n)=5(n^2-10mn+25m^2)-6(4n^2-12mn+9m^2)-(21m^2-3mn-7mn+n^2)=5n^2-50mn+125m^2-24n^2+72mn-54m^2-21m^2+10mn-n^2=-20n^2+32mn+50m^2

и) (x-y)^3=x^3-3x^2*y+3x*y^2-y^3

к) (2a-b)^3=8a^3-12a^2*b+6a*b^2-b^3